The Effect of Divalent Metal Ions on the Temperature Stability of Poly(I:C) Duplex - Evgeniya Usenko; Vladimir Valeev; Alexander Glamazda; Victor Karachevtsev (Journal of Spectroscopy)
The effect of divalent ions on the thermal stability of the double-stranded polynucleotide polyinosinic:polycytidylic acid (poly(I:C)) in a buffer solution (pH 7) was studied by UV absorption spectroscopy and thermal denaturation by measuring the absorbance at 260 nm. The concentration dependence of the polynucleotide melting temperature (Tm) in the presence of metal ions (2.5 × 10−6–10−2 M) was obtained. It was found that the duplex thermal stability grew gradually upon an increase of Ca2+ and Mn2+ concentration. The thermal stability of the duplex in the presence of Cd2+, Ni2+, and Zn2+ rises up to an ion concentration of about 10−4 M and further falls. In contrast to these ions, the addition of Cu2+ to the solution leads to a sharp decline in Тm of the duplex at a concentration above 10−5 M. The observed difference in the influence of metal ions on the poly(I:C) thermal stability is explained by the different affinity of these ions to both the phosphate groups and the nitrogenous bases of the polynucleotides. Based on the analysis of the Tm concentration dependence, the dominant binding of each ion to the specific polynucleotide components was proposed.